Ammonium dichromate poisoning: A rare cause of acute kidney injury - Radhakrishnan, H. (Indian J Nephrol, 2014)
Ammonium dichromate is an inorganic compound frequently used in screen and color printing. Being a strong oxidizing agent, it causes oxygen free radical injury resulting in organ failure. We report a 25-year-old female who presented with acute kidney injury after consumption of ammonium dichromate. She was managed successfully with hemodialysis and supportive measures. This case is reported to highlight the toxicity of ammonium dichromate.